Method for producing latex composition

By adding sulfur-based vulcanizing agent, xanthanic acid compound and strong acid salt-based surfactant to the latex of the conjugated diene polymer, a latex composition with excellent stability was prepared, which solved the problems of insufficient mechanical properties of the impregnated molded body and delayed allergic reactions in the prior art, and achieved excellent mechanical properties and safety.

CN115003733BActive Publication Date: 2025-04-11ZEON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180010384.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-20
Filing Date
2021-02-08
Publication Date
2025-04-11
Estimated Expiration
2041-02-08

AI Technical Summary

Technical Problem

In the prior art, when manufacturing impregnated molded bodies without vulcanization accelerators, it is difficult to achieve excellent tensile strength, tensile elongation and tear strength, and there is a risk of late-onset allergic reactions.

Method used

By adding a sulfur-based vulcanizing agent, a xanthanic acid compound and a strong acid salt-based surfactant to the latex of the conjugated diene polymer, a latex composition with excellent stability was prepared, and its mechanical properties were improved through the maturation process.

Benefits of technology

Excellent tensile strength, tensile elongation and tear strength of the impregnated molded body are achieved, while avoiding the occurrence of late-onset allergic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003757683270000331
    Figure BDA0003757683270000331
Patent Text Reader

Abstract

The present invention provides a method for producing a latex composition, comprising: a preparation step of preparing a latex of a conjugated diene polymer; and a preparation step of adding a sulfur-based vulcanizing agent, a xanthogenic acid compound and a strong acid salt-based surfactant to the latex of the conjugated diene polymer to obtain the latex composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a latex composition, and also relates to a method for producing a latex composition having excellent stability and capable of forming a film-molded body such as an impregnated body having excellent tensile strength, tensile elongation, and tear strength, and a method for producing an impregnated body using the latex composition obtained by such a production method. Background Art

[0002] It has long been known that a latex composition containing natural rubber latex can be dip-molded to obtain film-molded products such as pacifiers, balloons, gloves, air bags, and bags that are used in contact with the human body. However, since natural rubber latex contains proteins that cause immediate allergic reactions (type I) in humans, there are sometimes problems with dip-molded products that directly contact living mucous membranes or organs. Therefore, research is underway to remove proteins from natural rubber latex by purification or to use synthetic rubber latex instead of natural rubber.

[0003] For example, Patent Document 1 discloses a latex composition as a composition for dip molding, which is prepared by mixing zinc oxide, sulfur and a vulcanization accelerator in a latex of synthetic polyisoprene as a synthetic rubber. However, in the technology of Patent Document 1, although it is possible to prevent the occurrence of immediate allergies (Type I) caused by proteins from natural rubber, when a dip molded body is made, due to the vulcanization accelerator contained in the dip molded body, allergic symptoms of delayed allergies (Type IV) sometimes occur when it comes into contact with the human body. Moreover, in the case of not mixing with a vulcanization accelerator that causes delayed allergy (Type IV) symptoms, the tensile strength, tensile elongation, and tear strength of the obtained dip molded body are insufficient. Therefore, it is desired to improve the tensile strength, tensile elongation, and tear strength of the dip molded body in the case of not mixing with a vulcanization accelerator that causes delayed allergy (Type IV) symptoms.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: International Publication No. 2014 / 129547. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The present invention has been completed in view of such actual conditions, and its purpose is to provide a method for producing a latex composition having excellent stability and capable of forming film-molded bodies such as impregnated bodies having excellent tensile strength, tensile elongation, and tear strength, as well as a method for producing an impregnated body using the latex composition obtained by such a production method.

[0009] Solutions for solving problems

[0010] The present inventors have conducted intensive studies to achieve the above object and have found that the above object can be achieved by a step of adding a sulfur-based vulcanizing agent, a xanthogenic acid compound and a strong acid salt surfactant to a latex of a conjugated diene polymer, thereby completing the present invention.

[0011] That is, according to the present invention, a method for producing a latex composition is provided, comprising: a preparation step of preparing a latex of a conjugated diene polymer; and a preparation step of adding a sulfur-based vulcanizing agent, a xanthate compound and a strong acid salt-based surfactant to the latex of the above-mentioned conjugated diene polymer to obtain a latex composition.

[0012] In the above-mentioned preparation step of the method for producing the latex composition of the present invention, it is preferred that a strong acid salt surfactant is added in advance to the latex of the conjugated diene polymer, and then a sulfur-based vulcanizing agent and a xanthogenic acid compound are added to the latex of the conjugated diene polymer to which the strong acid salt surfactant is added.

[0013] In the method for producing a latex composition of the present invention, the strong acid salt surfactant is preferably used in an amount of 0.1 to 3 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.

[0014] In the method for producing a latex composition of the present invention, the strong acid salt-based surfactant is preferably a compound having a sulfonate group or a phosphate group.

[0015] In the method for producing a latex composition of the present invention, the strong acid salt-based surfactant is preferably a compound having a polycyclic structure.

[0016] In the method for producing a latex composition of the present invention, it is preferred that the latex of the conjugated diene polymer is a latex of a conjugated diene polymer having no carboxyl group.

[0017] In the method for producing a latex composition of the present invention, the latex of the conjugated diene polymer is preferably a latex of synthetic polyisoprene, a latex of a styrene-isoprene-styrene block copolymer, or a latex of a natural rubber from which protein has been removed.

[0018] In the method for producing the latex composition of the present invention, it is preferred that an aging step is further included after the above-mentioned preparation step, and the above-mentioned aging step is performed by aging the latex composition obtained in the above-mentioned preparation step by storing it at a temperature of 5 to 60° C. for 12 hours to 14 days, so that the pH of the above-mentioned latex composition after aging in the above-mentioned aging step is above 9.

[0019] In the method for producing a latex composition of the present invention, it is preferred that the pH of the latex composition after the preparation step and before the aging step be 10 or higher.

[0020] Furthermore, according to the present invention, there is provided a method for producing a dip-molded article, comprising the step of dip-molding the latex composition obtained by the above-mentioned production method.

[0021] Effects of the Invention

[0022] According to the present invention, there can be provided a method for producing a latex composition having excellent stability and capable of forming a film-molded body such as an impregnated body having excellent tensile strength, tensile elongation, and tear strength, as well as a method for producing an impregnated body using the latex composition obtained by such a production method. DETAILED DESCRIPTION

[0023] The method for producing the latex composition of the present invention comprises:

[0024] a preparation step of preparing a latex of a conjugated diene polymer; and

[0025] In the preparation step, a sulfur-based vulcanizing agent, a xanthogenic acid compound, and a strong acid salt-based surfactant are added to the latex of the conjugated diene polymer to obtain a latex composition.

[0026] The preparation step in the production method of the present invention is a step of preparing a latex of a conjugated diene polymer for use in the preparation step described below. The latex of a conjugated diene polymer used in the present invention is not particularly limited as long as it is a latex in which a conjugated diene polymer is dispersed in water.

[0027] <Latex of conjugated diene polymer>

[0028] The latex of the conjugated diene polymer used in the present invention is not particularly limited, and examples thereof include latex of synthetic polyisoprene, latex of styrene-isoprene-styrene block copolymer (SIS), latex of natural rubber from which protein has been removed (deproteinized natural rubber), latex of nitrile-containing conjugated diene copolymer, etc. Among these, latex of polymers containing isoprene units such as latex of synthetic polyisoprene, latex of SIS, and latex of deproteinized natural rubber are preferred, and latex of synthetic polyisoprene is particularly preferred. In addition, the latex of the conjugated diene polymer used in the present invention may have a modified group such as a carboxyl group, but from the viewpoint of being able to reduce the number of manufacturing steps, a latex of a conjugated diene polymer without a carboxyl group is preferred. In addition, the conjugated diene polymer having no carboxyl group may be any conjugated diene polymer that does not substantially have a carboxyl group, and may contain a carboxyl group in an amount caused by impurities (for example, an amount of less than about 0.05% by weight in terms of monomer units).

[0029] When a latex of synthetic polyisoprene is used as the latex of the conjugated diene polymer, the synthetic polyisoprene contained in the latex of synthetic polyisoprene may be a homopolymer of isoprene or a copolymer of isoprene and other ethylenically unsaturated monomers copolymerizable with isoprene. From the viewpoint of easily obtaining a film-molded product such as an impregnated product that is soft and has excellent tensile strength, the content of the isoprene unit in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, further preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene) relative to all monomer units.

[0030] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers such as styrene and alkylstyrene; ethylenically unsaturated carboxylic acid ester monomers such as methyl (meth)acrylate (referring to "methyl acrylate and / or methyl methacrylate", and the same also applies to ethyl (meth)acrylate, etc. hereinafter), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, etc. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination of two or more.

[0031] Synthetic polyisoprene can be obtained by a conventionally known method, for example, by solution polymerization of isoprene and other copolymerizable ethylenically unsaturated monomers used as required in an inert polymerization solvent using a Ziegler polymerization catalyst composed of trialkylaluminum-titanium tetrachloride or an alkyllithium polymerization catalyst such as n-butyllithium or sec-butyllithium. The polymer solution of synthetic polyisoprene obtained by solution polymerization can be directly used to produce synthetic polyisoprene latex, or the solid synthetic polyisoprene can be taken out from the polymer solution and dissolved in an organic solvent to produce synthetic polyisoprene latex.

[0032] In the case of obtaining a polymer solution of synthetic polyisoprene by the above method, impurities such as residues of the polymerization catalyst remaining in the polymer solution can be removed. In addition, an anti-aging agent described later can be added to the solution during or after polymerization. In addition, commercially available solid synthetic polyisoprene can also be used.

[0033] The isoprene units in the synthetic polyisoprene include four types, namely, cis-bonding units, trans-bonding units, 1,2-vinyl-bonding units, and 3,4-vinyl-bonding units, depending on the bonding form of the isoprene. From the viewpoint of increasing the tensile strength of the obtained film-molded product such as the impregnated molded product, the content ratio of the cis-bonding units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, relative to the total isoprene units.

[0034] The weight average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, based on standard polystyrene conversion according to gel permeation chromatography analysis. When the weight average molecular weight of the synthetic polyisoprene is within the above range, the tensile strength, tensile elongation, and tear strength of a film-molded article such as a dip-molded article tend to be further improved, and the synthetic polyisoprene latex tends to be easier to produce.

[0035] In addition, the polymer Mooney viscosity (ML) of synthetic polyisoprene 1+4 , 100°C) is preferably 50 to 80, more preferably 60 to 80, further preferably 70 to 80.

[0036] Examples of methods for obtaining synthetic polyisoprene latex include: (1) a method for producing synthetic polyisoprene latex by emulsifying a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier and removing the organic solvent as needed; (2) a method for directly producing synthetic polyisoprene latex by emulsion polymerization or suspension polymerization of isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith in the presence of an emulsifier. The production method (1) is preferred because synthetic polyisoprene having a high ratio of cis-bonded units in the isoprene units can be used and film-molded products such as dip-molded products having excellent mechanical properties such as tensile strength can be easily obtained.

[0037] Examples of the organic solvent used in the production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, and xylene; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, and cyclohexene; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; and halogenated hydrocarbon solvents such as dichloromethane, chloroform, and dichloroethane. Among these, alicyclic hydrocarbon solvents and aliphatic hydrocarbon solvents are preferred, pentane, cyclohexane, and n-hexane are more preferred, and n-hexane is particularly preferred.

[0038] The amount of the organic solvent used is preferably 2000 parts by weight or less, more preferably 20 to 1500 parts by weight, and even more preferably 500 to 1500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.

[0039] As the emulsifier used in the production method of the above (1), an ionic emulsifier is preferably used, and among them, an anionic emulsifier is more preferably used. Examples of the anionic emulsifier include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, sodium rosinate, and potassium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium hexadecylbenzenesulfonate, and potassium hexadecylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkylsulfuric acid ester salts such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; monoalkylphosphate ester salts such as sodium lauryl phosphate and potassium lauryl phosphate, etc.

[0040] Among these anionic emulsifiers, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfate ester salts and polyoxyethylene alkyl ether sulfate ester salts are preferred, and fatty acid salts and alkylbenzenesulfonates are particularly preferred.

[0041] In addition, from the viewpoint of being able to more effectively remove trace amounts of residual polymerization catalysts (particularly aluminum and titanium) from synthetic polyisoprene and suppressing the generation of coagulation products when preparing the latex composition, at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate ester salts, and polyoxyethylene alkyl ether sulfate ester salts and fatty acid salts can be used in combination. Here, as the fatty acid salt, sodium rosinate and potassium rosinate are preferred, and as the alkylbenzene sulfonate, sodium dodecylbenzene sulfonate and potassium dodecylbenzene sulfonate are preferred. In addition, these emulsifiers may be used alone or in combination of two or more.

[0042] In addition, as described above, by using at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and fatty acid salts in combination, the obtained latex will become a latex containing at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and fatty acid salts.

[0043] Examples of the ionic emulsifier other than the anionic emulsifier include copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkyl aryl ethers.

[0044] Furthermore, a nonionic emulsifier such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan alkyl ester may be used in combination as long as the coagulation by the coagulant used in the dip molding is not inhibited.

[0045] The amount of the emulsifier used in the manufacturing method of (1) above is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and further preferably 5 to 15 parts by weight relative to 100 parts by weight of synthetic polyisoprene. In addition, when two or more emulsifiers are used, it is preferred that their total amount be within the above range. That is, for example, when at least one selected from alkylbenzene sulfonate, alkyl sulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt and fatty acid salt are used in combination, it is preferred that their total amount be within the above range. By making the amount of the emulsifier used within the above range, the generation of agglomerates during emulsification can be further suppressed.

[0046] When at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt and polyoxyethylene alkyl ether sulfate ester salt and fatty acid salt are used in combination as anionic emulsifiers, the weight ratio of "fatty acid salt" : "the total weight of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt and polyoxyethylene alkyl ether sulfate ester salt" is preferably in the range of 1:1 to 10:1, and more preferably in the range of 1:1 to 7:1. When the weight ratio of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt and polyoxyethylene alkyl ether sulfate ester salt is within the above range, foaming generated during the treatment of synthetic polyisoprene can be suppressed, thereby eliminating the need for long-term standing and adding a defoaming agent, thereby contributing to improved workability and cost reduction.

[0047] The amount of water used in the production method (1) is preferably 10 to 1000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight relative to 100 parts by weight of the organic solvent solution of the synthetic polyisoprene. Examples of the type of water used include hard water, soft water, ion-exchanged water, distilled water, and zeolite water, with soft water, ion-exchanged water, and distilled water being preferred.

[0048] The apparatus for emulsifying a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier can be used without particular limitation as long as it is a commercially available emulsifier or disperser. The method of adding the emulsifier to the solution or fine suspension of synthetic polyisoprene is not particularly limited, and the emulsifier may be added in advance to water or to the solution or fine suspension of synthetic polyisoprene, or to both, or may be added to the emulsion during the emulsification operation, and may be added all at once or in batches.

[0049] Examples of the emulsifying device include batch emulsifiers such as "Homogenizer" (manufactured by Aika Co., Ltd.), "Polytron" (manufactured by Kinematica Co., Ltd.), and "TK AUTO Homomixer" (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.); "TK PIPELINE Homomixer" (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.), "Colloid Mill" (manufactured by Kobelco Pantec Co., Ltd.), "Thrasher" (manufactured by Nippon Cokes Industries Co., Ltd.), "Trigonal Wet Micro-Pulverizer" (manufactured by Mitsui Miike Chemical Industry Co., Ltd.), "Cavitron" (manufactured by Eurotec Co., Ltd.), "Milder" (manufactured by Pacific Machinery Co., Ltd.), and "Fine Flow" (manufactured by Fujikawa Chemical Industry Co., Ltd.). Mill" (manufactured by Pacific Machinery Co., Ltd.); high-pressure emulsifiers such as the product name "Microfluidizer" (manufactured by Minoga Industry Co., Ltd.), the product name "Nanomizer" (manufactured by NANOMIZER Co., Ltd.), and the product name "APVGaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as the product name "Membrane Emulsifier" (manufactured by Renka Industry Co., Ltd.); vibration emulsifiers such as the product name "Vibration Mixer (VIBROMIXER)" (manufactured by Renka Industry Co., Ltd.); ultrasonic emulsifiers such as the product name "Ultrasonic Homogenizer" (manufactured by Branson Co., Ltd.). In addition, the conditions for the emulsification operation using the emulsifying device are not particularly limited, and the processing temperature, processing time, etc. can be appropriately selected to achieve the desired dispersion state.

[0050] In the production method (1) above, it is desirable to remove the organic solvent from the emulsion obtained through the emulsification operation.

[0051] As a method for removing the organic solvent from the emulsion, a method is preferably used that can reduce the content of the organic solvent (preferably alicyclic hydrocarbon solvent or aliphatic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less. For example, reduced pressure distillation, atmospheric pressure distillation, steam distillation, centrifugal separation and the like can be used.

[0052] The organic solvent may be removed while adding a defoaming agent. By adding a defoaming agent, the foaming of the synthetic polyisoprene can be suppressed.

[0053] Furthermore, in order to increase the solid content concentration of the synthetic polyisoprene latex, after removing the organic solvent, a concentration operation can be carried out by using a method such as reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, etc. as needed. In particular, centrifugal separation is preferably carried out from the viewpoint of being able to increase the solid content concentration of the synthetic polyisoprene latex and simultaneously reduce the residual amount of the emulsifier in the synthetic polyisoprene latex.

[0054] Centrifugal separation is preferably carried out under the following conditions, for example: a continuous centrifuge is used, the centrifugal force is preferably 100 to 10,000 G, the solid content concentration of the synthetic polyisoprene latex before centrifugal separation is preferably 2 to 15% by weight, the flow rate into the centrifuge is preferably 500 to 1,700 kg / hr, and the back pressure (gauge pressure) of the centrifuge is preferably 0.03 to 1.6 MPa. Synthetic polyisoprene latex can be obtained as a light liquid after centrifugal separation. In addition, the residual amount of emulsifier in the synthetic polyisoprene latex can be reduced thereby.

[0055] The solid content concentration of the synthetic polyisoprene latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content concentration greater than the lower limit of the above range, the film-molded body such as the dip-molded body described later is not easily damaged. In addition, by making the solid content concentration less than the upper limit of the above range, the viscosity of the synthetic polyisoprene latex can be prevented from becoming too high, and it is easy to transport in a pipeline and stir in a mixing tank.

[0056] The volume average particle size of the synthetic polyisoprene latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm. By setting the volume average particle size within the above range, the latex viscosity becomes moderate and easy to handle, and the formation of a film on the surface of the latex can be suppressed during storage of the synthetic polyisoprene latex.

[0057] Furthermore, the synthetic polyisoprene latex may contain additives such as pH adjusters, defoamers, preservatives, crosslinking agents, chelating agents, deoxidizers, dispersants, and antioxidants that are commonly used in the field of latex.

[0058] Examples of the pH adjuster include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., but alkali metal hydroxides or ammonia are preferred. The pH of the synthetic polyisoprene latex in the preparation step is not particularly limited, but as described later, when a latex composition is prepared using the synthetic polyisoprene latex and the latex composition is aged under predetermined conditions, the pH of the latex composition before aging is preferably 10 or more.

[0059] As the latex of the conjugated diene polymer, as described above, a latex of a styrene-isoprene-styrene block copolymer (SIS) can also be used. In SIS, "S" represents a styrene block, and "I" represents an isoprene block.

[0060] SIS contained in SIS latex can be obtained by a conventionally known method, for example, using an active organic metal such as n-butyl lithium as an initiator to block copolymerize isoprene and styrene in an inactive polymerization solvent. In addition, the obtained SIS polymer solution can be directly used to manufacture SIS latex, but it is also possible to take out solid SIS from the polymer solution and dissolve the solid SIS in an organic solvent to manufacture SIS latex. There is no particular limitation on the method for manufacturing SIS latex, but the following method is preferred: in the presence of an emulsifier, a solution or a fine suspension of SIS dissolved or finely dispersed in an organic solvent is emulsified in water, and the organic solvent is removed as needed to manufacture SIS latex.

[0061] At this time, impurities such as residues of the polymerization catalyst remaining in the polymer solution can be removed after synthesis. In addition, an anti-aging agent described later can also be added to the solution during or after polymerization. In addition, commercially available solid SIS can also be used.

[0062] As the organic solvent, the same organic solvent as in the case of synthesizing polyisoprene can be used, but an aliphatic hydrocarbon solvent is preferred, and n-hexane is particularly preferred.

[0063] The amount of the organic solvent used is usually 50 to 2000 parts by weight, preferably 80 to 1000 parts by weight, more preferably 100 to 500 parts by weight, and further preferably 150 to 300 parts by weight, based on 100 parts by weight of SIS.

[0064] As the emulsifier, the same emulsifiers as in the case of synthesizing polyisoprene can be exemplified, and anionic emulsifiers are preferred, and potassium rosinate and sodium dodecylbenzenesulfonate are particularly preferred.

[0065] The amount of the emulsifier used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and even more preferably 5 to 15 parts by weight relative to 100 parts by weight of SIS. When the amount of the emulsifier used is within the above range, the stability of the obtained latex can be improved.

[0066] The amount of water used in the above-mentioned method for producing SIS latex is preferably 10 to 1000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight relative to 100 parts by weight of the organic solvent solution of SIS. Examples of the type of water used include hard water, soft water, ion exchange water, distilled water, zeolite water, and the like. In addition, a polar solvent represented by an alcohol such as methanol may be used in combination with water.

[0067] The apparatus for emulsifying the organic solvent solution or fine suspension of SIS in water in the presence of an emulsifier may be the same apparatus as in the case of synthesizing polyisoprene. The method for adding the emulsifier is not particularly limited, and the emulsifier may be added in advance to water, or to the organic solvent solution or fine suspension of SIS, or to both, or may be added to the emulsion during the emulsification operation, and may be added all at once or in batches.

[0068] In the above-mentioned method for producing SIS latex, it is preferred to obtain SIS latex by removing the organic solvent from the emulsified product obtained by the emulsification operation. The method for removing the organic solvent from the emulsified product is not particularly limited, and methods such as reduced pressure distillation, atmospheric pressure distillation, steam distillation, centrifugal separation, etc. can be used.

[0069] The organic solvent may be removed while adding a defoaming agent. Adding a defoaming agent can suppress foaming.

[0070] In order to increase the solid content concentration of the SIS latex, after removing the organic solvent, a concentration operation may be performed as necessary by using a method such as reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, etc.

[0071] The solid content concentration of the SIS latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content concentration greater than the lower limit of the above range, a film-molded body such as an impregnated body described later is not easily damaged. In addition, by making the solid content concentration less than the upper limit of the above range, the viscosity of the SIS latex can be prevented from becoming too high, and it is easy to transport in a pipeline and to stir in a mixing tank.

[0072] In addition, the SIS latex may be formulated with additives such as a pH adjuster, a defoamer, a preservative, a crosslinking agent, a chelating agent, a scavenger, a dispersant, an anti-aging agent, etc., which are commonly formulated in the field of latex. Examples of the pH adjuster include the same pH adjusters as those in the case of the above-mentioned synthetic polyisoprene, preferably an alkali metal hydroxide or ammonia. In addition, the pH of the SIS latex in the preparation step is not particularly limited, but as described later, when a latex composition is prepared using SIS latex and the latex composition is aged under prescribed conditions, the pH of the latex composition before aging is preferably 10 or more.

[0073] The content of the styrene units in the styrene blocks in the SIS contained in the SIS latex thus obtained is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and even more preferably 100% by weight, based on all monomer units.

[0074] The content of the isoprene units in the isoprene block in SIS is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and even more preferably 100% by weight, based on all monomer units.

[0075] The content ratio of styrene units to isoprene units in SIS is generally 1:99 to 90:10, preferably 3:97 to 70:30, more preferably 5:95 to 50:50, and even more preferably 10:90 to 30:70, in terms of the weight ratio of "styrene units:isoprene units".

[0076] The weight average molecular weight of SIS is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000, based on standard polystyrene conversion according to gel permeation chromatography. When the weight average molecular weight of SIS is within the above range, the balance between tensile strength and flexibility of a film-molded body such as an impregnated body is improved, and the latex of SIS tends to be easy to manufacture.

[0077] The volume average particle size of the latex particles (SIS particles) in the SIS latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm. When the volume average particle size of the latex particles is within the above range, the latex viscosity becomes moderately easy to handle, and the formation of a film on the latex surface can be suppressed when the SIS latex is stored.

[0078] Moreover, as the latex of the conjugated diene polymer, as described above, a latex of a nitrile group-containing conjugated diene copolymer can also be used.

[0079] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing an ethylenically unsaturated nitrile monomer and a conjugated diene monomer, and may be a copolymer obtained by copolymerizing other ethylenically unsaturated monomers copolymerizable with these monomers as needed.

[0080] As conjugated diene monomers, for example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene and chloroprene can be cited. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content ratio of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile-containing conjugated diene copolymer is preferably 56 to 78 weight %, more preferably 56 to 73 weight %, and further preferably 56 to 68 weight %. By making the content of the conjugated diene monomer unit within the above range, the tensile strength of the obtained film-molded body such as the impregnated body can be made sufficient, while the feel and elongation are more excellent.

[0081] As the ethylenically unsaturated nitrile monomer, as long as it is an ethylenically unsaturated monomer containing a nitrile group, there is no particular limitation, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Acrylonitrile and methacrylonitrile are particularly preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The proportion of the ethylenically unsaturated nitrile monomer units formed by the ethylenically unsaturated nitrile monomers in the nitrile-containing conjugated diene copolymer is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and further preferably 30 to 40% by weight. By making the content of the ethylenically unsaturated nitrile monomer units within the above range, the tensile strength of the film-molded bodies such as the obtained impregnated bodies can be made sufficient, while making the feel and elongation more excellent.

[0082] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include: vinyl aromatic monomers such as styrene, alkyl styrene, and vinyl naphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, dibutyl fumarate, and diethyl maleate Ethylenically unsaturated carboxylic acid ester monomers such as methoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; crosslinking monomers such as divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate. These ethylenically unsaturated monomers can be used alone or in combination of two or more.

[0083] The content of other monomer units composed of other ethylenically unsaturated monomers in the nitrile group-containing conjugated diene copolymer is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably 3% by weight or less.

[0084] The nitrile group-containing conjugated diene copolymer can be obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, preferably by emulsion polymerization. As the emulsion polymerization method, a conventionally known method can be adopted.

[0085] When the monomer mixture containing the above monomers is subjected to emulsion polymerization, commonly used polymerization auxiliary materials such as emulsifiers, polymerization initiators, molecular weight regulators, etc. can be used. The method for adding these polymerization auxiliary materials is not particularly limited, and can be any method of initial one-time addition method, batch addition method, continuous addition method, etc.

[0086] There is no particular limitation on the emulsifier, and examples thereof include: nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters; anionic emulsifiers such as alkylbenzene sulfonates such as potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate, higher alcohol sulfate ester salts, and alkyl sulfosuccinates; cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzyl ammonium chloride; copolymeric emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. Anionic emulsifiers are particularly preferred, alkylbenzene sulfonates are more preferred, and potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate are particularly preferred. These emulsifiers can be used alone or in combination of two or more. The amount of the emulsifier used is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of the monomer mixture.

[0087] The polymerization initiator is not particularly limited, and examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-tert-butyl peroxide, di-α-isopropylbenzene peroxide, acetyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, and more preferably 0.01 to 2 parts by weight, relative to 100 parts by weight of the monomer mixture.

[0088] In addition, the peroxide initiator can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, and examples thereof include compounds containing metal ions in a reduced state such as ferrous sulfate and cuprous cyclopentaneate; sulfonic acid compounds such as sodium methanesulfonate; amine compounds such as dimethylaniline, etc. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight relative to 100 parts by weight of the peroxide.

[0089] The amount of water used in the emulsion polymerization is preferably 80 to 600 parts by weight, particularly preferably 100 to 200 parts by weight, based on 100 parts by weight of all the monomers used.

[0090] As a method for adding monomers, for example, there can be mentioned: a method of adding the monomers to be used to the reaction container at one time; a method of adding continuously or intermittently as the polymerization proceeds; a method of adding a part of the monomers and reacting to a specific conversion rate, and then continuously or intermittently adding the remaining monomers to polymerize, etc. Any method can be used. In the case of mixing the monomers and adding them continuously or intermittently, the composition of the mixture can be fixed or can also be changed. In addition, with respect to each monomer, the various monomers to be used can be mixed in advance and added to the reaction container, or can also be added to the reaction container separately.

[0091] Furthermore, polymerization auxiliary materials such as a chelating agent, a dispersant, a pH adjuster, a deoxidizing agent, and a particle size adjuster may be used as necessary, and the type and amount of these materials used are not particularly limited.

[0092] The polymerization temperature during emulsion polymerization is not particularly limited, but is usually 3 to 95° C., preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.

[0093] When the monomer mixture is subjected to emulsion polymerization as described above and a predetermined polymerization conversion rate is reached, the polymerization system is cooled or a polymerization terminator is added to terminate the polymerization reaction. The polymerization conversion rate when the polymerization reaction is terminated is preferably 90% by weight or more, more preferably 93% by weight or more.

[0094] The polymerization terminator is not particularly limited, and examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, aromatic hydroxydithiocarboxylic acids such as hydroxydimethylbenzenethiocarboxylic acid, hydroxydiethylbenzene dithiocarboxylic acid, and hydroxydibutylbenzene dithiocarboxylic acid and their alkali metal salts, and alcohols such as methanol, ethanol, and isopropanol. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight relative to 100 parts by weight of the monomer mixture.

[0095] After the polymerization reaction is terminated, unreacted monomers may be removed as desired, and the solid content concentration and pH may be adjusted to obtain a latex of a nitrile group-containing conjugated diene copolymer.

[0096] Furthermore, an anti-aging agent, a preservative, an antibacterial agent, a dispersant, etc. may be appropriately added to the latex of the nitrile group-containing conjugated diene copolymer as required.

[0097] The number average particle size of the latex of the nitrile group-containing conjugated diene copolymer is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by adjusting the amount of the emulsifier and the polymerization initiator used.

[0098] In addition, as the latex of the conjugated diene polymer, as described above, a latex of natural rubber from which proteins have been removed (deproteinized natural rubber) can also be used. As the latex of the deproteinized natural rubber, a latex known as so-called "deproteinized natural rubber latex" obtained by a known protein removal method can be used, and the above-mentioned known protein removal method is a method of removing proteins in natural rubber latex by, for example, a protease, a surfactant, etc., and washing, centrifugation, etc.

[0099] As the conjugated diene polymer used in the present invention, as described above, synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), nitrile-containing conjugated diene copolymer, deproteinized natural rubber, etc. can be used, but are not limited to these. Butadiene polymers, styrene-butadiene copolymers, etc. can also be used.

[0100] The butadiene polymer may be a homopolymer of 1,3-butadiene as a conjugated diene monomer, or a copolymer obtained by copolymerizing 1,3-butadiene as a conjugated diene monomer and another ethylenically unsaturated monomer copolymerizable therewith.

[0101] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing 1,3-butadiene and styrene as conjugated diene monomers, and may be a copolymer obtained by copolymerizing other ethylenically unsaturated monomers copolymerizable with these monomers as needed.

[0102] The conjugated diene polymer latex used in the present invention may contain additives such as a pH adjuster, a defoamer, a preservative, a chelating agent, a deoxidizer, a dispersant, and an antioxidant, which are usually added in the field of latex.

[0103] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., but alkali metal hydroxides or ammonia are preferred. In addition, the pH of the conjugated diene polymer latex in the preparation step is not particularly limited, but in the production method of the present invention, as described later, when a xanthogenic acid compound and a sulfur-based vulcanizing agent are added to the conjugated diene polymer latex to prepare a latex composition and the latex composition is aged under predetermined conditions, the pH of the latex composition before aging is preferably 10 or more.

[0104] In order to increase the solid content concentration of the latex of the conjugated diene polymer, a concentration operation can be carried out as needed by a method such as reduced pressure distillation, atmospheric distillation, centrifugal separation, membrane concentration, etc. From the viewpoint of being able to adjust the residual amount of the emulsifier in the latex of the conjugated diene polymer, centrifugal separation is preferably carried out.

[0105] When the conjugated diene polymer latex is placed in a centrifuge, a pH adjuster is preferably added in advance to adjust the pH of the latex to 7 or higher, more preferably 9 or higher, in order to improve the mechanical stability of the latex.

[0106] The solid content concentration of the latex of the conjugated diene polymer used in the present invention is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content concentration within the above range, the generation of aggregates in the latex can be more effectively suppressed, and the separation of polymer particles during storage of the latex can be more effectively suppressed.

[0107] <Preparation process>

[0108] In the production method of the present invention, a sulfur-based vulcanizing agent, a xanthogenic acid compound, and a strong acid salt-based surfactant are added to the above-mentioned latex of the conjugated diene polymer to prepare a latex composition containing them (preparation step).

[0109] Here, by making the latex of the conjugated diene polymer contain a sulfur-based vulcanizing agent and a xanthate compound, since the xanthate compound does not cause delayed hypersensitivity (type IV), the occurrence of delayed hypersensitivity (type IV) can be effectively suppressed. On the other hand, the present inventors have found that when the latex composition containing the xanthate compound is aged (pre-crosslinked) and then used to produce a film-formed body such as a dip-formed body, the amount of coagulation in the latex composition increases, making it difficult to perform dip molding. In particular, when a conjugated diene polymer that does not contain a carboxyl group is used as the latex of the conjugated diene polymer, this problem tends to become more significant.

[0110] In this regard, the present inventors have conducted in-depth research and found that by adding a strong acid salt surfactant when adding a sulfur-based vulcanizing agent and a xanthate compound to the latex of a conjugated diene polymer, such a problem can be effectively solved. In particular, the present inventors have conducted in-depth research and found that when a xanthate compound is added to the latex of a conjugated diene polymer, the pH will decrease when the obtained latex composition is ripened (pre-crosslinked), thereby damaging the stability of the latex composition, and as a result, the amount of coagulation in the latex composition increases. The decrease in pH during ripening is a unique phenomenon that can be observed when a xanthate compound is added. It is not limited to a specific theory, but it can be considered that one of the reasons for the decrease in pH during ripening is the decomposition of the xanthate compound. In this regard, the present invention finds that by adding a sulfur-based vulcanizing agent and a xanthate compound to the latex of a conjugated diene polymer, a strong acid salt surfactant is further added, and even when the pH of the latex composition is reduced during ripening, the stability of the latex composition can be maintained, and the above-mentioned problem can be solved as a result.

[0111] The sulfur-based vulcanizing agent is not particularly limited, and examples thereof include sulfur such as powdered sulfur, sublimated sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur; sulfur compounds such as sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-disulfo-bis(hexahydro-2H-azepine-2)), phosphorus-containing polysulfide, polymer polysulfide, and 2-(4'-morpholinodisulfo)benzothiazole. Among these, sulfur can be preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.

[0112] The amount of the sulfur-based vulcanizing agent used is not particularly limited, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 3 parts by weight, and even more preferably 1 to 2 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the latex composition. By making the content of the sulfur-based vulcanizing agent within the above range, the occurrence of delayed hypersensitivity (IV type) symptoms can be suppressed in the obtained film-molded article, such as the dip-molded article, and the tensile strength can be further improved.

[0113] The xanthate compound used in the present invention acts as a vulcanization accelerator by being used in combination with a sulfur-based vulcanizing agent. That is, when a sulfur-based vulcanizing agent is added to a latex composition, and the conjugated diene polymer in the latex composition is vulcanized by the sulfur-based vulcanizing agent to form a film-formed body such as an impregnated molded body, the xanthate compound acts as a vulcanization accelerator. In addition, the xanthate compound acts as a vulcanization accelerator in a latex composition containing a sulfur-based vulcanizing agent, and after vulcanization, it is decomposed into alcohol and carbon disulfide by heat applied during vulcanization. For example, the xanthate compound is decomposed into alcohol and carbon disulfide by heat applied during the manufacture of a film-formed body (heat of about 100 to 130° C. when vulcanizing a conjugated diene polymer), and then the components generated by the decomposition (alcohol and carbon disulfide, etc.) volatilize. As a result, the residual amount of the xanthate compound in the obtained film-formed body is reduced. That is, in the method for producing the latex composition of the present invention, since a vulcanization accelerator (e.g., a dithiocarbamate-based vulcanization accelerator, a thiazole-based vulcanization accelerator, etc.) that conventionally causes delayed hypersensitivity (type IV) symptoms is not used, a xanthate compound is used as a vulcanization accelerator, thereby reducing the residual amount of the xanthate compound in the obtained film-formed product such as the dip-formed product, and thus the occurrence of delayed hypersensitivity (type IV) symptoms in the obtained film-formed product can be suppressed.

[0114] The xanthogenic acid compound used in the present invention is not particularly limited, and examples thereof include xanthogenic acid, xanthogenic acid salts, xanthogenic acid disulfide (a compound in which two xanthogenic acids are bonded via a sulfur atom or the like), and xanthogenic acid polysulfide (a compound in which three or more xanthogenic acids are bonded via a sulfur atom or the like).

[0115] Xanthate is not particularly limited as long as it has a xanthate structure, and examples thereof include compounds represented by the general formula (ROC(=S)S)x-Z (wherein R is a linear or branched hydrocarbon, and Z is a metal atom. x is a number consistent with the valence of Z, and is usually 1 to 4, preferably 2 to 4, and particularly preferably 2).

[0116] The xanthate represented by the general formula (ROC(=S)S)x-Z is not particularly limited, and examples thereof include zinc dimethyl xanthate, zinc diethyl xanthate, zinc dipropyl xanthate, zinc diisopropyl xanthate, zinc dibutyl xanthate, zinc diamyl xanthate, zinc dihexyl xanthate, zinc diheptyl xanthate, zinc dioctyl xanthate, zinc di(2-ethylhexyl) xanthate, zinc didecyl xanthate, zinc didodecyl xanthate, potassium dimethyl xanthate, potassium ethyl xanthate, propyl xanthate, Xanthate, potassium isopropyl xanthate, potassium butyl xanthate, potassium amyl xanthate, potassium hexyl xanthate, potassium heptyl xanthate, potassium octyl xanthate, potassium 2-ethylhexyl xanthate, potassium decyl xanthate, potassium dodecyl xanthate, sodium methyl xanthate, sodium ethyl xanthate, sodium propyl xanthate, sodium isopropyl xanthate, sodium butyl xanthate, sodium amyl xanthate, sodium hexyl xanthate, sodium heptyl xanthate, sodium octyl xanthate, sodium 2-ethylhexyl xanthate, sodium decyl xanthate, sodium dodecyl xanthate, etc. Among these, xanthate in the general formula (ROC(=S)S)x-Z is preferably 2 or more, isopropyl xanthate and butyl xanthate are more preferred, and diisopropyl zinc xanthate and dibutyl zinc xanthate are particularly preferred. These xanthates may be used alone or in combination of two or more.

[0117] Xanthogenic acid disulfide is a compound in which two xanthogenic acids are bonded via a sulfur atom or the like. It is not particularly limited and examples thereof include dimethyl xanthogenic acid disulfide, diethyl xanthogenic acid disulfide, diisopropyl xanthogenic acid disulfide, dibutyl xanthogenic acid disulfide, polymethyl xanthogenic acid sulfide, polyethyl xanthogenic acid sulfide, polyisopropyl xanthogenic acid sulfide, and polybutyl xanthogenic acid sulfide. Among these, diisopropyl xanthogenic acid disulfide and dibutyl xanthogenic acid disulfide are preferred.

[0118] Polysulfide xanthogenic acid is a compound in which three or more xanthogenic acids are bonded via a sulfur atom or the like, and examples thereof include trisulfide xanthogenic acid in which three xanthogenic acids are bonded via sulfur, tetrasulfide xanthogenic acid in which four xanthogenic acids are bonded via sulfur, and pentasulfide xanthogenic acid in which five xanthogenic acids are bonded via sulfur.

[0119] In addition, these xanthate compounds may be contained in the latex composition alone, or preferably in two or more forms. For example, when xanthate is added to the latex composition, a portion of the added xanthate exists in the form of a xanthate, and as a result, two or more xanthate compounds may be contained in the latex composition. Alternatively, a portion of the xanthate added to the latex composition may exist in the form of xanthate disulfide or xanthate polysulfide through the action of the sulfur-based vulcanizing agent in the latex composition. Similarly, even when xanthate, xanthate disulfide or xanthate polysulfide are added to the latex composition, these may exist in the form of any one of xanthate, xanthate, xanthate disulfide or xanthate polysulfide, respectively.

[0120] The amount of the xanthogenic compound used (when a plurality of xanthogenic compounds are included, the total amount used) is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, further preferably 0.5 to 5 parts by weight, and further preferably 1 to 3 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the latex. When the amount of the xanthogenic compound used is within the above range, the occurrence of delayed hypersensitivity (IV type) symptoms can be suppressed in the obtained film-molded article, such as the dip-molded article, and the tensile strength can be further improved.

[0121] In the present invention, it is preferred that the latex composition contains substantially no compounds conventionally used as vulcanization accelerators other than xanthic acid compounds, specifically, sulfur-containing vulcanization accelerators (e.g., dithiocarbamate-based vulcanization accelerators, thiazole-based vulcanization accelerators, etc.) that cause delayed hypersensitivity (type IV) symptoms and remain in the obtained film-molded body such as the dip-molded body after functioning as a vulcanization accelerator.

[0122] As the strong acid salt surfactant used in the present invention, as long as it has a structure of a salt composed of a strong acid and a strong base and has a surface active effect, there is no particular limitation, and examples thereof include: compounds with a sulfonate group, compounds with a sulfate group or a sulfate ester salt group, compounds with a phosphate group or a phosphate ester salt group, compounds with a nitrate group, etc. Among these, preferably a compound with a sulfonate group, a compound with a phosphate group or a phosphate ester salt group, more preferably a compound with a sulfonate group or a compound with a phosphate group. In addition, these strong acid salt surfactants can be used alone or in combination of multiple types.

[0123] The compound having a sulfonate group as the strong acid salt-based surfactant is not particularly limited as long as it is a compound having a salt structure in which a sulfonic group is neutralized by a strong base, and examples thereof include sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF), sodium alkylbenzenesulfonate, sodium 1-hexanesulfonate, trisodium naphthalenetrisulfonate, and the like.

[0124] The compound having a sulfate group or a sulfate ester salt group as the strong acid salt-based surfactant is not particularly limited as long as it is a compound having a salt structure in which the sulfate group or the sulfate ester group is neutralized by a strong base, and examples thereof include sodium lauryl sulfate.

[0125] The compound having a phosphate group or a phosphate ester group as the strong acid salt-based surfactant is not particularly limited as long as it has a salt structure in which the phosphate group or the phosphate ester group is neutralized by a strong base, and examples thereof include sodium lauryl phosphate and potassium lauryl phosphate.

[0126] In addition, as the strong acid salt surfactant used in the present invention, it is also possible to have a compound with a polycyclic structure. As a polycyclic structure, as long as there is a structure with more than two ring structures, it is not particularly limited, and for example, a biphenyl structure as a structure in which two benzene rings are connected by a single bond, a condensed polycyclic structure formed by condensing (contracting) more than two monocyclic rings, etc. can be cited. The ring constituting the polycyclic structure can be either an alicyclic ring or an aromatic ring, and in addition, heteroatoms can also be included. In addition, the number of rings is not particularly limited, and is preferably more than two rings, and from practicality, its upper limit is about ten rings. As a condensed polycyclic structure, for example: dicyclopentadiene structure, naphthalene structure, fluorene structure, anthracene structure, phenanthrene structure, triphenylene structure, pyrene structure, ovalbenzene structure, etc. can be cited.

[0127] Examples of strong acid salt-based surfactants having a polycyclic structure include β-naphthalenesulfonic acid formaldehyde condensate sodium salt (NASF), sodium naphthalenesulfonate, disodium naphthalene disulfonate, trisodium naphthalene trisulfonate, sodium butyl naphthalene sulfonate, etc. Among these, β-naphthalenesulfonic acid formaldehyde condensate sodium salt (NASF) which is a compound having a sulfonate group and a polycyclic structure is preferred.

[0128] The amount of the strong acid salt surfactant used is preferably 0.01 to 5 parts by weight, more preferably 0.1 to 4 parts by weight, further preferably 0.1 to 3 parts by weight, further preferably 0.5 to 3 parts by weight, and particularly preferably 0.8 to 1.5 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex. By making the amount of the strong acid salt surfactant used within the above range, the tensile strength, tensile elongation and tear strength of the obtained film-formed bodies such as the impregnated bodies can be further improved. In addition, when preparing the latex of the conjugated diene polymer, when using a strong acid salt surfactant as an emulsifier, the above-mentioned amount used is the amount after removing the amount of the strong acid salt surfactant used as the emulsifier.

[0129] That is, for example, as a latex of a conjugated diene polymer, a solution or fine suspension of a conjugated diene polymer is emulsified in water in the presence of an emulsifier, the organic solvent is removed as needed, and the solid content concentration is adjusted to 30 to 70% by weight (more preferably 40 to 70% by weight, further preferably 50 to 70% by weight) by concentration, thereby obtaining a latex of a conjugated diene polymer. When using the latex of the conjugated diene polymer, the amount of the strong acid salt surfactant used after removing the organic solvent to adjust the solid content concentration to 30 to 70% by weight (more preferably 40 to 70% by weight, further preferably 50 to 70% by weight) is preferably within the above-mentioned range.

[0130] There is no particular limitation on the method of adding a sulfur-based vulcanizing agent, a xanthate compound, and a strong acid salt surfactant to the latex of the above-mentioned conjugated diene polymer. The sulfur-based vulcanizing agent, the xanthate compound, and the strong acid salt surfactant may be added in the order of the sulfur-based vulcanizing agent, the xanthate compound, and the strong acid salt surfactant, or they may be added simultaneously. Alternatively, after the strong acid salt surfactant is added in advance, the sulfur-based vulcanizing agent and the xanthate compound may be added in the order of the xanthate compound and the sulfur-based vulcanizing agent. In particular, from the viewpoint that the stability can be made better even if the pH of the latex composition is reduced due to the addition of the xanthate compound, it is preferred to adopt the method of adding the sulfur-based vulcanizing agent and the xanthate compound after the strong acid salt surfactant is added in advance. In addition, the order of adding the sulfur-based vulcanizing agent and the xanthate compound at this time is not particularly limited. Either one may be added first, or they may be added simultaneously. In addition, the sulfur-based vulcanizing agent, the xanthate compound, and the strong acid salt surfactant may also be added in the form of an aqueous solution or an aqueous dispersion.

[0131] In the production method of the present invention, in addition to adding the sulfur-based vulcanizing agent, the xanthogenic acid compound and the strong acid salt-based surfactant to the latex of the conjugated diene polymer, an activator may be added as needed.

[0132] By adding an activator to the latex composition, when the conjugated diene polymer in the latex composition is vulcanized using a sulfur-based vulcanizing agent to prepare a film-formed product such as a dip-formed product, the activator acts as a vulcanization accelerator together with the above-mentioned xanthogenic acid compound, thereby further improving the tear strength of the obtained film-formed product such as the dip-formed product.

[0133] As activator, it is not particularly limited. From the viewpoint of further improving the tear strength of film-formed bodies such as the obtained impregnated body, it is preferred to use a metal compound. As metal compound, it is not particularly limited. For example, metal oxides, metal compounds containing at least one carbon atom, etc. can be cited. As the metal constituting the metal compound, it is not particularly limited. Main group metals (at least one element selected from the 1st group element, the 2nd group element, the 12th group element, the 13th group element, the 14th group element, the 15th group element, the 16th group element, the 17th group element and the 18th group element) are preferred, and 2nd group element, 12th group element, 13th group element, and 14th group element are more preferred. Zinc, magnesium, calcium, aluminum, and lead are further preferred. Zinc, magnesium, and calcium are particularly preferred, and zinc is most preferred. These metal compounds can be used alone or in combination.

[0134] The metal oxide is not particularly limited, but from the viewpoint of further improving the tear strength of the obtained film-molded body such as the dip-molded body, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, lead oxide, iron oxide, copper oxide, tin oxide, nickel oxide, chromium oxide, cobalt oxide, and aluminum oxide are preferred, and zinc oxide is more preferred.

[0135] As the metal compound containing at least one carbon atom, carbonates, bicarbonates, hydroxides, and organometallic compounds are preferred from the viewpoint of further improving the tear strength of the obtained film-formed body such as the impregnated body, and carbonates, bicarbonates, and organometallic compounds are more preferred. Among these, inorganic salts such as carbonates and bicarbonates are particularly preferred from the viewpoint of excellent stability of the compound itself and excellent ease of acquisition.

[0136] The amount of the activator used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 1 to 3 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the latex composition. By setting the amount of the activator used within the above range, the tear strength of the obtained film-molded body such as the impregnated body can be further improved.

[0137] The method for blending the activator is not particularly limited as long as it is a method that ultimately results in a state where the latex of the conjugated diene polymer and the activator are mixed.

[0138] Furthermore, a vulcanization accelerator may be further added to the latex composition within a range that can suppress the occurrence of delayed hypersensitivity (type IV) symptoms in the obtained film-molded article or the like.

[0139] As the vulcanization accelerator, a vulcanization accelerator commonly used in dip molding can be used, and examples thereof include dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, and dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc, 2-Mercaptothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthiocarbamoylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholinodithio)benzothiazole, 4-morpholino-2-benzothiazole disulfide, 1,3-bis(2-benzothiazolylmercaptomethyl)urea, etc. The vulcanization accelerator can be used alone or in combination of two or more.

[0140] Furthermore, the latex composition may further contain the following compounding agents as needed: an anti-aging agent; a dispersant; a reinforcing agent such as carbon black, silica, talc, etc.; a filler such as calcium carbonate, clay, etc.; an ultraviolet absorber; a plasticizer, etc.

[0141] Examples of the antioxidant include phenolic antioxidants not containing sulfur atoms, such as 2,6-di-4-methylphenol, 2,6-di-tert-butylphenol, butylhydroxyanisole, 2,6-di-tert-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, styrenated phenol, 2,2'-methylene-bis(6-α-methylbenzyl-p-cresol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), alkylated bisphenols, and butylated reaction products of p-cresol and dicyclopentadiene; 2,2'-thiobis-(4-methyl-6-tert-butylphenol), 4,4'-thiobis-(6-tert-butyl-o-cresol), 2,6-di-tert-butyl Thiobisphenol antioxidants such as tris(nonylphenyl) phosphite, diphenyl isodecyl phosphite, tetraphenyl dipropylene glycol diphosphite, etc.; phosphite antioxidants such as dilauryl thiodipropionate, amine antioxidants such as phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamino)diphenylamine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, butyraldehyde-aniline condensate, etc.; quinoline antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, etc.; hydroquinone antioxidants such as 2,5-di-tert-amylhydroquinone, etc. These anti-aging agents can be used alone or in combination of two or more.

[0142] The content of the antioxidant is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 1 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer.

[0143] There are no particular limitations on the method of mixing various compounding agents in the latex composition, and examples thereof include: after obtaining a composition containing a latex of a conjugated diene polymer, a sulfur-based vulcanizing agent, a xanthate compound, and a strong acid salt surfactant as described above, using a dispersing machine such as a ball mill, a kneader, and a disperser to mix various compounding agents as needed in the obtained composition; after obtaining a composition containing a latex of a conjugated diene polymer and a strong acid salt surfactant, using the above-mentioned dispersing machine to prepare an aqueous dispersion of compounding ingredients other than the latex of a conjugated diene polymer and the strong acid salt surfactant, and then mixing the aqueous dispersion with the latex composition containing the latex of a conjugated diene polymer and the strong acid salt surfactant, etc. In addition, at least a portion of the various compounding agents may also be mixed after aging as described later.

[0144] The solid content concentration of the latex composition of the present invention is preferably 10 to 60% by weight, more preferably 10 to 55% by weight.

[0145] <Aging process>

[0146] In the present invention, the latex composition thus obtained is preferably aged (pre-crosslinked). The conditions for the aging are not particularly limited, and for example, the aging can be performed by storing at a temperature of 5 to 60°C for 12 hours to 14 days. In the present invention, the pH of the latex composition before aging is preferably adjusted to 10 or more, more preferably to 11 or more, and further preferably to 12 or more. By making the pH of the latex composition before aging within the above range, the stability of the latex composition after aging can be further improved. In addition, the upper limit of the pH of the latex composition before aging is not particularly limited, but is preferably 14 or less, and more preferably 13.5 or less.

[0147] The aging temperature is preferably 5 to 60° C., more preferably 10 to 30° C., and even more preferably 10 to 25° C. When the aging temperature is within the above range, the mechanical strength of the obtained film molded body such as the impregnated molded body can be further improved.

[0148] The aging time depends on the aging temperature, but is preferably 12 hours to 14 days, more preferably 12 hours to 10 days, and even more preferably 12 hours to 7 days. By setting the aging time within the above range, the mechanical strength of the obtained film molded body such as the impregnated molded body can be further improved.

[0149] In the present invention, the pH of the latex composition after aging is preferably 9 or more, more preferably 9.5 or more, and even more preferably 10 or more. When the pH of the latex composition after aging is too low, the stability of the latex composition after aging is reduced, and thus a large amount of aggregation may occur in the latex composition. In addition, the upper limit of the pH of the latex composition after aging is not particularly limited, but is preferably 14 or less, and more preferably 13.5 or less.

[0150] In addition, since the latex composition produced by the present invention contains a xanthate compound, there is a tendency for the pH of the latex composition to decrease due to aging. According to the present invention, a strong acid salt-based surfactant is added in addition to the xanthate compound, thereby suppressing the decrease in stability of the latex composition caused by such a decrease in pH. On the other hand, although the decrease in stability of the latex composition caused by such a decrease in pH can be effectively alleviated when a strong acid salt-based surfactant is added, it is preferred not to reduce the pH of the latex composition. Therefore, when the pH of the latex composition decreases due to aging, the pH can be adjusted to the above range by adding a pH adjuster to the latex composition after aging or during aging. There is no particular limitation on the timing of adding the pH adjuster to the latex composition after aging or during aging, but it is preferably added within 24 hours after the start of aging, and more preferably within 12 hours after the start of aging.

[0151] The pH adjuster added to the latex composition after or during aging is not particularly limited, and examples thereof include: alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., preferably alkali metal hydroxides, ammonia or organic amine compounds. These pH adjusters can be used alone or in combination of two or more.

[0152] According to the method for producing a latex composition of the present invention, by making the latex composition contain a latex of a conjugated diene polymer, a sulfur-based vulcanizing agent, a xanthate compound and a strong acid salt-based surfactant, the stability of the latex composition itself can be made excellent, and at the same time, the obtained film-formed bodies such as dip-formed bodies can suppress the occurrence of delayed hypersensitivity (type IV) symptoms, and at the same time, the tensile strength, tensile elongation, and tear strength can be made excellent.

[0153] <Impregnation molding>

[0154] In the method for producing a dip-molded article of the present invention, a dip-molded article can be obtained by dip-molding a latex composition obtained by the above-mentioned method of the present invention. The dip-molding method is as follows: a mold is dipped into a latex composition, the composition is deposited on the surface of the mold, and then, after the mold is lifted from the composition, the composition deposited on the surface of the mold is dried. In addition, the mold before being dipped in the latex composition can be preheated. In addition, before dipping the mold in the latex composition or after the mold is lifted from the latex composition, a coagulant can be used as needed.

[0155] Specific examples of the method of using the coagulant include a method in which the mold before being immersed in the latex composition is immersed in a solution of the coagulant to allow the coagulant to adhere to the mold (anodic coagulation immersion method); a method in which the mold on which the latex composition is deposited is immersed in a coagulant solution (Teague coagulation immersion method), etc. From the perspective of being able to obtain an immersion-molded body with less uneven thickness, the anodic coagulation immersion method is preferred.

[0156] Specific examples of the coagulant include metal halides such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates such as barium nitrate, calcium nitrate, and zinc nitrate; acetates such as barium acetate, calcium acetate, and zinc acetate; and sulfates such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Calcium salts are particularly preferred, and calcium nitrate is more preferred. These water-soluble multivalent metal salts can be used alone or in combination of two or more.

[0157] The coagulant can be used as a solution of water, alcohol or a mixture thereof, and is preferably used in the form of an aqueous solution. The aqueous solution may further contain a water-soluble organic solvent such as methanol or ethanol, and a nonionic surfactant. The concentration of the coagulant varies depending on the type of the water-soluble multivalent metal salt, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight.

[0158] After the mold is lifted from the latex composition, the deposit formed on the mold is usually dried by heating. The drying conditions can be appropriately selected.

[0159] Next, heating is performed to crosslink the dip-molded layer formed on the mold. The crosslinking of the dip-molded layer can usually be performed by heat treatment at a temperature of 80 to 150°C, preferably for 10 to 130 minutes. As a heating method, external heating using infrared rays or hot air or internal heating using high-frequency waves can be used. External heating using hot air is particularly preferred. In addition, before the heat treatment, the dip-molded layer can be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (for example, remaining emulsifiers, coagulants, etc.). The removal of water-soluble impurities can also be performed after the dip-molded layer is heat-treated, but from the perspective of being able to more effectively remove water-soluble impurities, it is preferably performed before the heat treatment.

[0160] Then, the dip-molded body can be obtained by separating the dip-molded layer from the dip-molding die. As a method of separation, it is possible to adopt a method of peeling it from the molding die by hand, or to peel it by pressure of water or compressed air. In addition, after the separation, it can be further heated at a temperature of 60 to 120° C. for 10 to 120 minutes.

[0161] The film thickness of the dip-molded body is preferably 0.03 to 0.50 mm, more preferably 0.05 to 0.40 mm, particularly preferably 0.08 to 0.30 mm.

[0162] The dip molded article obtained by the production method of the present invention is a dip molded article obtained by using the above-mentioned latex composition, so the delayed hypersensitivity (IV type) symptoms can be suppressed, and the tensile strength, tensile elongation and tear strength can be excellent, and it can be particularly preferably used as a glove. In the case where the film molded article is a glove, in order to prevent the film molded articles from being closely attached to each other at the contact surface and to improve the lubricity when putting on and taking off, inorganic fine particles such as talc and calcium carbonate or organic fine particles such as starch particles can be sprinkled on the surface of the glove, or an elastic layer containing fine particles can be formed on the surface of the glove, and the surface layer of the glove can be chlorinated.

[0163] Furthermore, the dip-molded article obtained by the production method of the present invention can be used for medical products such as nipples for baby bottles, glass straws, tubes, cold water pads, inflatable air bags, medical catheters, condoms, etc., toys such as balloons, dolls, balls, etc., industrial products such as bags for pressurized molding and gas storage bags, finger cots, etc., in addition to the above-mentioned gloves.

[0164] Example

[0165] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the following "parts" are weight references. In addition, various physical properties are measured in the following manner.

[0166] <Solid content concentration>

[0167] 2 g of the sample (weight: X2) was accurately weighed in an aluminum pan (weight: X1) and dried in a hot air dryer at 105°C for 2 hours. After cooling in the dryer, the weight of the sample together with the aluminum pan was measured (weight: X3), and the solid content concentration was calculated according to the following calculation formula.

[0168] Solid content concentration (weight %) = (X3-X1) × 100 / X2

[0169] <Content of aggregates>

[0170] The solid content concentration of the latex composition is measured according to the above method. After accurately weighing about 100 g of the latex composition, it is filtered through a 200-mesh SUS metal mesh of known weight, and the coagulation on the metal mesh is washed with water several times to remove the latex composition. After drying it at 105°C for 60 minutes, its dry weight is measured, and the content of the coagulation is calculated as a ratio when the amount of the polymer component contained in the latex composition is 100% by weight (unit: weight %). The less the content of the coagulation, the better the stability of the latex composition.

[0171] <Tensile strength and tensile elongation of dip-molded articles>

[0172] Based on ASTM D412, the impregnated molded body was punched out with a dumbbell cutter (trade name "Super Dumbbell (model: SDMK-100C)", manufactured by DUMBBELL Co., Ltd.) to prepare a test piece for tensile strength measurement. The test piece was stretched at a tensile speed of 500 mm / min using a universal tensile testing machine (trade name "RTG-1210", manufactured by ORIENTEC Co., Ltd.), and the tensile strength just before breaking (unit: MPa) and the tensile elongation just before breaking (unit: %) were measured.

[0173] <Tear Strength of Dip Molded Article>

[0174] Based on ASTM D624-00, the impregnated molded body was placed in a constant temperature and humidity chamber at 23°C and a relative humidity of 50% for more than 24 hours, and then punched out with a dumbbell cutter (trade name "Die C", manufactured by DUMBBELL Co., Ltd.) to prepare a test piece for measuring tear strength. The test piece was stretched at a tensile speed of 500 mm / min using a universal tensile testing machine (trade name "RTG-1210", manufactured by A&D Co., Ltd.) to measure the tear strength (unit: N / mm).

[0175] <Example 1>

[0176] (Production of Latex of Synthetic Polyisoprene (A-1))

[0177] 900 parts of n-hexane and 100 parts of isoprene were placed in a dry, nitrogen-substituted autoclave with a stirrer. The temperature in the autoclave was set to 60°C, and while stirring, 0.05 parts of a n-hexane solution containing 15% by weight of n-butyl lithium as a catalyst solution was added, and the mixture was reacted for 1 hour to obtain a reaction solution. The polymerization reaction rate was 99%. Methanol was added to the obtained reaction solution as a polymerization terminator to stop the reaction, thereby obtaining a n-hexane solution (a-1) of synthetic polyisoprene with a weight average molecular weight (Mw) of 1,840,000 (solid content concentration 10% by weight).

[0178] On the other hand, potassium rosinate was added to water and dissolved by heating it to 60°C to prepare an emulsifier aqueous solution (b-1) having a concentration of 1.5% by weight.

[0179] Next, the n-hexane solution of synthetic polyisoprene (a-1) and the aqueous emulsifier solution (b-1) obtained above were mixed using a mixer (product name "Multi-channel mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the amount of synthetic polyisoprene in the n-hexane solution of synthetic polyisoprene (a-1) and the amount of potassium rosinate in the aqueous emulsifier solution (b-1) were 10 parts per 100 parts, and then mixed and emulsified using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.) at a rotation speed of 4100 rpm to obtain an emulsified dispersion (c-1). In this case, the total feed flow rate of the n-hexane solution of synthetic polyisoprene (a-1) and the aqueous emulsifier solution (b-1) was 2000 kg / hr, the temperature was 60°C, and the back pressure (gauge pressure) was 0.5 MPa.

[0180] Next, the obtained emulsified dispersion (c-1) was heated to 80°C under a reduced pressure of -0.01 to -0.09 MPa (gauge pressure), and the n-hexane was distilled off to obtain an aqueous dispersion (d-1) of synthetic polyisoprene. At this time, a defoamer (trade name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while spraying so that the amount of the defoamer was 300 ppm by weight relative to the synthetic polyisoprene in the emulsified dispersion (c-1). In addition, when the n-hexane was distilled off, the emulsified dispersion (c-1) was adjusted to less than 70% by volume of the tank volume, and a three-stage inclined paddle blade was used as a stirring blade, and stirring was slowly carried out at 60 rpm.

[0181] After the distillation of n-hexane was completed, the obtained aqueous dispersion of synthetic polyisoprene (d-1) was centrifuged at 8000 to 9000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to concentrate the aqueous dispersion, thereby obtaining a latex of synthetic polyisoprene (A-1) having a solid content concentration of 60% by weight as a light liquid. The centrifugal separation was performed under the following conditions: the solid content concentration of the aqueous dispersion (d-1) before centrifugation was 8% by weight, the flow rate during the continuous centrifugation was 1300 kg / hr, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa. In addition, in the obtained latex of synthetic polyisoprene (A-1), potassium rosinate remained in an amount of 1 part per 100 parts of the synthetic polyisoprene (A-1) in the latex of synthetic polyisoprene (A-1). In addition, the synthetic polyisoprene (A-1) did not substantially contain a carboxyl group.

[0182] (Preparation of latex composition)

[0183] While stirring the latex of the synthetic polyisoprene (A-1) obtained above, sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF, product name "DEMOL T-45", manufactured by Kao Corporation) as a strong acid salt-based surfactant was added so that the amount of the sodium salt of β-naphthalenesulfonic acid formaldehyde condensate in terms of solid content was 1.0 part per 100 parts of the synthetic polyisoprene (A-1) in the latex of the synthetic polyisoprene (A-1). Then, while stirring the obtained mixture, an aqueous dispersion of each compounding ingredient was added so that, based on the solid content conversion amount, 2.5 parts of diisopropyl zinc xanthate as a xanthogenic acid compound, 1.5 parts of zinc oxide, 1.5 parts of sulfur, and 2 parts of an antioxidant (product name "Wingstay L", manufactured by Goodyear Co., Ltd.) were present relative to 100 parts of the synthetic polyisoprene (A-1) in the mixture. Thereafter, an aqueous potassium hydroxide solution (concentration: 5.0 wt%) was added to obtain a latex composition whose pH was adjusted to 12.5 (the pH of the latex composition before aging was 12.5).

[0184] (Maturation of latex composition)

[0185] Then, the obtained latex composition was aged for 48 hours in a constant temperature water tank adjusted to 30°C. In addition, a potassium hydroxide aqueous solution (concentration 5.0 weight%) was added to the latex composition 12 hours after the start of aging to adjust the pH of the latex composition to 12.1. In addition, 12 hours after the start of aging, the pH of the latex composition before the addition of the potassium hydroxide aqueous solution was 11.6, and the pH of the latex composition after aging for 48 hours was 11.8.

[0186] (Manufacturing of Impregnated Molded Article)

[0187] A commercially available ceramic hand-shaped mold (manufactured by Shinko Corporation) was cleaned, preheated in an oven at 70°C, immersed in a coagulant aqueous solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "Emulgen 109P", manufactured by Kao Corporation) for 5 seconds, and then taken out of the coagulant aqueous solution. Next, the hand-shaped mold was dried in an oven at 70°C for more than 30 minutes to allow the coagulant to adhere to the hand-shaped mold, and the hand-shaped mold was covered with the coagulant.

[0188] After that, the hand-shaped mold coated with the coagulant is taken out of the oven and immersed in the latex composition obtained after aging for 48 hours for 10 seconds. Next, the hand-shaped mold is air-dried at room temperature for 10 minutes, and then immersed in warm water at 60°C for 5 minutes to dissolve water-soluble impurities, forming a dip-molded layer on the hand-shaped mold. After that, the dip-molded layer formed on the hand-shaped mold is heated in an oven at a temperature of 130°C for 30 minutes to cross-link it, and then cooled to room temperature, sprinkled with talc, and then peeled off from the hand-shaped mold to obtain a dip-molded body (rubber glove). Then, according to the above method, the obtained dip-molded body (rubber glove) is evaluated for the coagulant content, tensile strength, tensile elongation, and tear strength. The results are shown in Table 1. In addition, the appearance of the obtained dip-molded body (rubber glove) is good and there are no special problems (the same is true in the examples described later).

[0189] <Example 2>

[0190] A latex composition before aging having a pH of 11.1 was obtained in the same manner as in Example 1 except that the amount of the pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Example 2, a potassium hydroxide aqueous solution (concentration 5.0% by weight) was added to the latex composition 12 hours after the start of aging to adjust the pH of the latex composition to 11.0. In addition, 12 hours after the start of aging, the pH of the latex composition before the addition of the potassium hydroxide aqueous solution was 10.4, and the pH of the latex composition after aging for 48 hours was 10.8. Then, using the latex composition after aging for 48 hours, a dip molded body (rubber glove) was produced in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.

[0191] <Example 3>

[0192] A latex composition before aging having a pH of 11.1 was obtained in the same manner as in Example 1 except that the amount of the pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Example 3, no pH adjuster (potassium hydroxide aqueous solution) was added to the latex composition 12 hours after the start of aging. In addition, the pH of the latex composition 12 hours after the start of aging was 10.4, and the pH of the latex composition after aging was 10.1. Then, using the latex composition after aging for 48 hours, a dip molded body (rubber glove) was manufactured in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 1.

[0193] <Example 4>

[0194] (Production of latex of synthetic polyisoprene (A-2))

[0195] 900 parts of n-hexane and 100 parts of synthetic polyisoprene (manufactured by Japan Zeon Co., Ltd., trade name "IR2200L", synthetic polyisoprene that is polymerized by a Ti-Al polymerization catalyst and substantially does not contain a carboxyl group) were placed in a dry and nitrogen-substituted autoclave equipped with a stirrer. Then, the temperature was raised to 60°C while stirring to dissolve the synthetic polyisoprene, thereby obtaining a n-hexane solution (a-2) of synthetic polyisoprene (solid content concentration: 10% by weight). The weight average molecular weight of the synthetic polyisoprene in the n-hexane solution was 1,210,000.

[0196] On the other hand, a linear alkylbenzene sulfonate was added to water, and the temperature was raised to 60° C. to dissolve the solution, thereby preparing an emulsifier aqueous solution (b-2) having a concentration of 1.0% by weight.

[0197] Next, the n-hexane solution of synthetic polyisoprene (a-2) and the aqueous emulsifier solution (b-2) obtained above were mixed using a mixer (product name "Multi-channel mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the linear alkylbenzene sulfonate in the aqueous emulsifier solution (b-2) was 10 parts per 100 parts of the synthetic polyisoprene in the n-hexane solution of synthetic polyisoprene (a-2), and then mixed and emulsified at a rotation speed of 4100 rpm using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.), thereby obtaining an emulsified dispersion (c-2). In this case, the total feed flow rate of the n-hexane solution of synthetic polyisoprene (a-2) and the aqueous emulsifier solution (b-2) was 2000 kg / hr, the temperature was 60°C, and the back pressure (gauge pressure) was 0.5 MPa.

[0198] Next, the obtained emulsified dispersion (c-2) was heated to 80°C under a reduced pressure of -0.01 to -0.09 MPa (gauge pressure), and the n-hexane was distilled off to obtain an aqueous dispersion (d-2) of synthetic polyisoprene. At this time, a defoamer (trade name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while spraying so that the amount of the defoamer was 300 ppm by weight relative to the synthetic polyisoprene in the emulsified dispersion (c-2). In addition, when the n-hexane was distilled off, the emulsified dispersion (c-2) was adjusted to less than 70% by volume of the tank volume, and a three-stage inclined paddle blade was used as a stirring blade, and stirring was slowly carried out at 60 rpm.

[0199] After the distillation of n-hexane was completed, the obtained aqueous dispersion of synthetic polyisoprene (d-2) was centrifuged at 8000 to 9000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to concentrate the aqueous dispersion, thereby obtaining a latex of synthetic polyisoprene (A-2) having a solid content concentration of 60% by weight as a light liquid. The centrifugal separation was performed under the following conditions: the solid content concentration of the aqueous dispersion (s-2) before centrifugation was 8% by weight, the flow rate during continuous centrifugation was 1300 kg / hr, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa. In addition, in the latex of synthetic polyisoprene (A-2), 1 part of linear alkylbenzene sulfonic acid remained with respect to 100 parts of the synthetic polyisoprene (A-2) in the latex of synthetic polyisoprene (A-2). In addition, the synthetic polyisoprene (A-2) did not substantially contain a carboxyl group.

[0200] (Preparation of latex composition)

[0201] While stirring the latex of the synthetic polyisoprene (A-2) obtained above, sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF, product name "DEMOL T-45", manufactured by Kao Corporation) as a strong acid salt-based surfactant was added so that the amount of the sodium salt of β-naphthalenesulfonic acid formaldehyde condensate in terms of solid content was 1.0 part per 100 parts of the synthetic polyisoprene (A-2) in the latex of the synthetic polyisoprene (A-2). Then, while stirring the obtained mixture, an aqueous dispersion of each compounding ingredient was added so that, based on the solid content conversion amount, 2.5 parts of diisopropyl zinc xanthate as a xanthogenic acid compound, 1.5 parts of zinc oxide, 1.5 parts of sulfur, and 2 parts of an antioxidant (product name "Wingstay L", manufactured by Goodyear Co., Ltd.) were present relative to 100 parts of the synthetic polyisoprene (A-2) in the mixture. Then, an aqueous potassium hydroxide solution (concentration: 5.0 wt%) was added to obtain a latex composition whose pH was adjusted to 10.8 (the pH of the latex composition before aging was 10.8).

[0202] (Maturation of latex composition)

[0203] Then, the obtained latex composition was aged for 48 hours in a constant temperature water tank adjusted to 30° C. The pH of the latex composition was 10.1 12 hours after the start of aging, and the pH of the latex composition was 9.8 after aging for 48 hours.

[0204] (Manufacturing of Impregnated Molded Article)

[0205] Then, a dip-molded article (rubber glove) was produced in the same manner as in Example 1 except that a latex composition containing synthetic polyisoprene (A-2) was used instead of the latex composition containing synthetic polyisoprene (A-1), and the same evaluation was performed. The results are shown in Table 1.

[0206] <Comparative Example 1>

[0207] A latex composition before aging having a pH of 9.5 was obtained in the same manner as in Example 1 except that sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF) was not added to the latex composition before aging and the amount of the pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Comparative Example 1, the pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition 12 hours after the start of aging. In addition, the pH of the latex composition 12 hours after the start of aging was 8.3, and the pH of the latex composition after aging was 8.1. In addition, in the latex composition obtained in Comparative Example 1, the generation of coagulation was significant (amount of coagulation: 52.5% by weight), and it was impossible to produce an impregnated molded body. The results are shown in Table 1.

[0208] <Comparative Example 2>

[0209] A latex of synthetic polyisoprene (A-2) was obtained in the same manner as in Example 4 except that the conditions for centrifuging the aqueous dispersion of synthetic polyisoprene (d-2) using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) were changed to 7000 to 8000 G, a flow rate during continuous centrifugation of 2000 kg / hr, and a back pressure (gauge pressure) of the centrifuge of 0.12 MPa. In the obtained latex of synthetic polyisoprene (A-2), 2 parts of linear alkylbenzene sulfonic acid remained with respect to 100 parts of the synthetic polyisoprene (A-2) in the latex of synthetic polyisoprene (A-2).

[0210] Next, while stirring the latex of the synthetic polyisoprene (A-2) obtained above, an aqueous dispersion of each compounding ingredient was added so that, based on solid content conversion, 2.5 parts of diisopropyl zinc xanthate as a xanthogenic acid compound, 1.5 parts of zinc oxide, 1.5 parts of sulfur, and 2 parts of an antioxidant (product name "Wingstay L", manufactured by Goodyear Co., Ltd.) were present in the latex of the synthetic polyisoprene (A-2) to 100 parts of the synthetic polyisoprene (A-2) in the latex. Thereafter, an aqueous potassium hydroxide solution (concentration: 5.0 wt%) was added to obtain a latex composition whose pH was adjusted to 9.8 (the pH of the latex composition before aging was 9.8).

[0211] Then, the obtained latex composition was aged for 48 hours in a constant temperature water tank adjusted to 30°C. The pH of the latex composition 12 hours after the start of aging was 8.8, and the pH of the latex composition after aging was 8.5. In addition, in the latex composition obtained in Comparative Example 2, the generation of coagulation was significant (amount of coagulation: 27.5% by weight), and it was impossible to produce an impregnated molded body. The results are shown in Table 1.

[0212] [Table 1]

[0213] Table 1

[0214]

[0215] As shown in Table 1, the latex composition obtained by adding a sulfur-based vulcanizing agent, a xanthate compound, and a strong acid salt surfactant to the prepared conjugated diene polymer latex has excellent stability and can suppress the generation of coagulation. Furthermore, when the latex composition is made into a dip-molded article, the obtained dip-molded article has excellent tensile strength, tensile elongation, and tear strength (Examples 1 to 4). In addition, since the obtained latex composition does not contain a vulcanization accelerator that causes delayed hypersensitivity (type IV) symptoms, it is believed that the obtained dip-molded article can prevent the generation of delayed hypersensitivity (type IV) when it is made into a dip-molded article.

[0216] On the other hand, when a latex composition was prepared without adding a strong acid salt surfactant to the conjugated diene polymer latex, the stability of the latex composition was poor, a large amount of coagulation occurred, and a dip molded article could not be produced (Comparative Example 1).

[0217] Furthermore, even when a strong acid salt surfactant is used during emulsification in the process of obtaining the conjugated diene polymer latex and the strong acid salt surfactant remains in the conjugated diene polymer latex, when the strong acid salt surfactant is not added when the sulfur vulcanizing agent and the xanthogenic acid compound are added, the stability of the prepared latex composition is poor, a large amount of coagulants are generated, and an impregnated molded body cannot be produced (Comparative Example 2).

Claims

1. A method for producing a latex composition, comprising: A preparation step of preparing a latex of a conjugated diene polymer; The preparation step comprises adding a sulfur-based vulcanizing agent, a xanthate compound and a strong acid salt-based surfactant to the latex of the conjugated diene polymer to obtain a latex composition; as well as an aging step, after the preparation step, aging the latex composition obtained in the preparation step by storing it at a temperature of 5 to 60° C. for 12 hours to 14 days, The conjugated diene polymer latex is a conjugated diene polymer latex having no carboxyl group, and the pH of the latex composition after aging in the aging step is set to 9 or more.

2. The method for producing a latex composition according to claim 1, wherein In the preparation step, after a strong acid salt surfactant is added to the latex of the conjugated diene polymer in advance, a sulfur-based vulcanizing agent and a xanthogenic acid compound are added to the latex of the conjugated diene polymer to which the strong acid salt surfactant is added.

3. The method for producing a latex composition according to claim 1 or 2, wherein: The strong acid salt-based surfactant is used in an amount of 0.1 to 3 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the latex of the conjugated diene polymer.

4. The method for producing a latex composition according to claim 1 or 2, wherein: The strong acid salt surfactant is a compound having a sulfonate group or a phosphate group.

5. The method for producing a latex composition according to claim 1 or 2, wherein: The strong acid salt surfactant is a compound with a polycyclic structure.

6. The method for producing a latex composition according to claim 1 or 2, wherein: The conjugated diene polymer latex is a latex of synthetic polyisoprene, a latex of a styrene-isoprene-styrene block copolymer, or a latex of a natural rubber from which proteins have been removed.

7. The method for producing a latex composition according to claim 1 or 2, wherein: The pH of the latex composition after the preparation step and before the aging step is set to 10 or more. 8 . A method for producing a dip-molded article, comprising the step of dip-molding the latex composition obtained by the production method according to claim 1 .

Citation Information

Patent Citations

  • Latex for dip molding use, composition for dip molding use, and dip-molded article

    WO2014129547A1

  • Latex composition

    WO2019039523A1

  • Production method for latex composition

    WO2019058807A1